Avaliação de diferentes modelos de biodigestores para tratamento de resíduos sólidos urbanos gerados no Restaurante Universitário da UFPB - Bezerra, Gabriela Pecorelli Figueiredo (2016)
The urban solid waste is one of the main environmental problems noticed nowadays. Through time the models of treatment and destination of residues (waste) more commonly used were incineration and landfill. Landfill, specifically, generates, from the decomposition of the organic fraction, solid urban waste gases which can be used in the production of energy. This generation of gas can also be in smaller scale using biodigesters, attending the demands of small communities, such as Universidade Federal da Paraíba Campus I. Within this context, this work aims to evaluate and compare the functioning of biodigesters to determine the most adequate solution for implantation at UFPB Campus I using organic waste from the University restaurant. Nowadays the university restaurant's waste is sent to Aterro Sanitário Metropolitano de João Pessoa, a landfill, generating a daily average of 513,77kg of organic waste. For the analysis of a more adequate model, some criteria were considered, such as the facility and cost of implantation, operation mode, efficiency in treatment, income and applied technology, being selected the following: Biodigester in batch (simplified model), Indian Biodigester, Chinese Biodigester, Ferreira’s Biodigestor (2015), Fernandes’s Biodigestor (2013) and Reis’s Biodigestor (2012), which were compared in terms of Moisture Content and the efficiency in removal of solids, Temperature, Organic Loading Rate, Potential of Hydrogen, alkalinity, production and concentration of methane. It was found that the biodigesters in batch (simplified model), Indian and Chinese, were not adequate for attending the proposed objective. After analyzing the diverse parameters, it was found that many can be used for comparison. The analysis of the moisture content and the efficiency of removal of volatile contents, such as temperature were not considered as parameters of decision for choosing the best option, since they all had similar characteristics. The organic loading rate for the biodigesters with batch supply did not present itself as a limiting factor, however, for the continuous supply, which is the case of the Ferreira (2015) model, it interfered directly in its functioning. In terms of pH, Ferreira (2015) had maintenance difficulties, Reis (2012) managed to stabilize it and Fernandes (2013), although obtained high values, understood to be within the acceptable and propitious pH levels to the production of biogas. The concentration of methane in the Ferreira (2015) model presented average values of 59%, while Reis (2012) and Fernandes (2013) obtained average methane concentration near 70%, presenting itself more efficient. Given that, the biodigester of Reis (2012) model presented itself as the more viable for reproduction at UFPB Campus I for the ends of production of biogas from the decomposition of waste generated at the university restaurant, having the necessity of implantation of 13 biodigesters as a way to a semiannual generation source.